Biodiversity and Distribution of Reticulitermes in the Southeastern USA - Allison Johnson; Brian T. Forschler (Insects, 2022)
Reticulitermes subterranean termites are widely distributed ecosystem engineers and structural pests, yet describing their species distribution worldwide or regionally has been hindered by taxonomic uncertainties. Morphological plasticity confounds the use of taxonomic keys, while recent species descriptions and molecular techniques lacking taxonomic support have caused a muddle in interpreting the literature on Reticulitermes species distributions. We employed an integrative taxonomic approach combining behavioral, morphological, and molecular techniques to identify 4371 Reticulitermes samples to species. Five Reticulitermes species were collected from wood-on-ground at 1570 sites covering 153,900 km2 in the state of Georgia, USA. Three species were collected throughout Georgia, with R. flavipes identified from every one of the 159 counties. R. nelsonae was the second most frequently collected species, found in 128 counties, with R. virginicus third with 122. Two species had distributions confined to the northern part of the state. R. malletei was collected from 73 counties, while the least collected species, R. hageni, was found in 16. Results show that the most recently described species (R. nelsonae, 2012) is widely distributed and the second-most frequently encountered termite, representing 23% of all samples. The invasive species R. flavipes represented half of all the samples collected, while R. hageni, the least at less than 1%. A search of GenBank identified a number of accessions mismatched to a species designation resulting in the literature under-reporting the biodiversity of the genus. We, therefore, outline a path to standardize methods for species identification using an integrated taxonomic approach with appropriate barcodes for consistent identification across research teams worldwide. The data also illuminate new opportunities to examine questions related to the ecology, evolution, dispersal, and resource partitioning behaviors of these sympatric species across distinct geographical regions.